2014
DOI: 10.1139/cjpp-2013-0226
|View full text |Cite
|
Sign up to set email alerts
|

Membrane potential differences and GABAA receptor expression in hepatic tumor and non-tumor stem cells

Abstract: The ability to differentiate tumor initiating stem cells (TISCs) from healthy, normal stem cells (NSCs) could have important diagnostic and therapeutic implications for patients with hepatocellular carcinoma (HCC). The aim of this study was to document and compare cell membrane potentials (PDs) and GABAA receptor subunit expression in hepatic TISCs and NSCs. PD values were determined in CD133(+) Huh-7 TISCs and CD133(+) WBF344 NSCs by single channel microelectrode impalement. GABAA receptor subunit expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
(22 reference statements)
1
3
1
Order By: Relevance
“…Malignant or cancer stem cells have been previously documented to have depolarized cell membrane potentials, increased proliferative activity and high telomerase levels. 8,14,15 In the present study, none of these features developed in HBV-infected NSCs. Future studies in which NSCs are cultured for periods beyond 30 days are required to more definitively determine whether HBV infection of NSCs ultimately results in the acquisition of these features and/or their predisposition to malignant transformation.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…Malignant or cancer stem cells have been previously documented to have depolarized cell membrane potentials, increased proliferative activity and high telomerase levels. 8,14,15 In the present study, none of these features developed in HBV-infected NSCs. Future studies in which NSCs are cultured for periods beyond 30 days are required to more definitively determine whether HBV infection of NSCs ultimately results in the acquisition of these features and/or their predisposition to malignant transformation.…”
Section: Discussioncontrasting
confidence: 58%
“…Changes in cell membrane PDs and in particular, a depolarized state is thought to play an important role in the malignant transformation of non-malignant cells including stem/progenitor cells. 8 In the present study, NSC PDs depolarized (became less negative) following exposure to HBV however, the depolarized state was transient with PD values returning to baseline by day 5 of infection ( Figure 5).…”
Section: Nsc Cytokine Membrane Potential Proliferation and Telomerasupporting
confidence: 37%
See 1 more Smart Citation
“…Altogether, existing evidence suggests that, in mice, ACBP is embedded in a circuit, where starvation stimulates autophagy, thereby causing ACBP release from cells. Secreted ACBP acts on gamma-aminobutyric acid A receptors (GABA A R) expressed on multiple cell types outside of the central nervous system (e.g., cholangiocytes, hepatocytes, and macrophages) [ 17 19 ] to cause a transient decrease in glycemia and the consequent activation of orexigenic circuitries [ 9 – 11 ], thus stimulating food intake and closing a homeostatic feedback loop or “hunger reflex” [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, GABRA4 might serve a role in COAD, which requires further study. Bautista et al (31) observed that the expression levels of GABRA6 in tumor initiating stem cells (TISCS) and hepatocellular carcinoma (HCC) were reduced, whereas the expression levels of GABRG3 were abundant in TISCS and limited in HCC. A previous study showed that the specific activation of GABA A receptor decreased cell activity, induced apoptosis and inhibited the growth and survival signal pathway of neuroblastoma cells (32).…”
Section: Discussionmentioning
confidence: 99%